Fast neutron scattering on carbon and oxygen - P. Mermod (2018)
© Copyright owned by the author(s) under the terms of the Creative Commons Attribution-NonCommercial-ShareAlike Licence. In fast neutron cancer therapy, more than 10% of the cell damage is expected to be caused by recoil nuclei from elastic and inelastic scattering. There are few data for these reactions in the intermediate energy region. Using the SCANDAL setup at The Svedberg Laboratory in Uppsala, we have measured differential cross sections for elastic scattering on carbon and oxygen at 95 MeV incident neutron energy, covering the angular range 10-85 (c.m.). We could also obtain differential cross sections for inelastic scattering reactions up to 12 MeV excitation energy. These data are shown to have a significant impact on the determination of recoil kerma coefficients.